SURG-33. IMMUNO-STIMULATION THROUGH SURGICALLY ADMINISTERED MECHANICAL HIGH INTENSITY FOCUSED ULTRASOUND. (11th November 2019) - Wang, James; Huang, Chin-Hsin; Echeagaray, Oscar; Amirfakhri, Siamak; Blair, Sarah; Trogler, William; Kummel, Andrew; Chen, Clark
Abstract: INTRODUCTION: While immunotherapy through anti-PD1 checkpoint inhibition has demonstrated impressive clinical efficacy against a number of tumor types, its application has been ineffective against glioblastomas. METHODS: We wished to determine whether high intensity focused ultrasound (HIFU) augment the efficacy of anti-PD1 checkpoint inhibition against glioblastomas. HIFU can be surgically administered through low-duty cycle to induce subcellular fragmentation without causing temperature elevation (termed mechanical HIFU). Alternatively, HIFU delivered through high duty cycle can induce foci of temperature elevation and thermal ablation (termed thermal HIFU). We tested the impact of mechanical and thermal HIFU on the anti-glioblastoma effects of the immune checkpoint inhibitor, ipililumab. RESULTS: In an in vivomurine glioblastoma model, sites targeted by mechanical HIFU exhibited a 10–100 fold increase in accumulation in tumor infiltrating lymphocytes and interferon-γ (IFN-γ) in the presence of PD-1 blockade. At least 75% of mice engrafted with glioblastomas achieved remission when treated with mechanical HIFU and PD-1 blockade. In contrast, none of the mice treated with single therapies achieved durable remission. Likelihood of remission correlated with the abundance of tumor infiltrating lymphocytes (p< 0.001) and IFN- γ levels (p=0.001). The synergy observed between mechanical HIFU and PD-1 blockade was not seen when combining thermal HIFU and PD-1 blockade, suggesting thermal protein denaturation is prohibitive to immune-stimulatory effects of HIFU. CONCLUSION: Mechanical HIFU, but not thermal HIFU, augments the anti-glioblastoma effects of PD-1 blockade. Our findings inform the utility of HIFU as an immune-adjuvant in glioblastoma therapy that can be surgically administered.